Fluxo transnacional de dados: estruturas, políticas e o direito nas vertentes da governança - Luiza Couto Chaves Brandão (2020)
The diversity of perspectives in historically state-centered negotiation and decisionmaking spaces is a complex factor that characterizes the idea of governance, more specifically in its relation to the transformations that law faces from technology. The work on international data flow seeks to place the theme among those that reflect not only the technical specificities of the internet but also the legal-political conflicts that are included in various international agendas. To this end, the discussion includes the structure upon which data flows operate, as well as their nature, on a global scale. Then, the internet governance model for the identification of the actors involved with the theme is presented, as well as the instruments discussed in the international agenda. The dynamics between state and non-state actors and the hypothesis of the transversality guide the observation of institutional designs for the regulation of data flow. Finally, we present the possible results or trends from the current scenario and the reflection of conflicts and geopolitical asymmetries on the transnational flow of data.